HIASAN DAN KALIGRAFI MAKAM SHADRUL AKABIR ‘ABDULLAH DI KABUPATEN ACEH UTARA - Nasral Yuzaili (Pascasarjana Institut Seni Indonesia Padang Panjang, 2018)
ABSTRACT The tomb of Shadrul Akabir ‘Abdullah is one of the remains of Samudra Pasai kingdom. That tomb was brought from Gujarat in the 15th century. The ornament on this tomb is the mixture of two cultures namely Hindu and Islamic cultures. The mixture of Hindu and Islam cultures on Shadrul Akabir Abdullah’s tomb can be seen on its ornament and calligraphy writing. This tomb has historical value through calligraphy writing, and it can reveal the history of Islam’s entrance to Aceh. The mixture of those two cultures leaves the cultural traces that are interesting to be revealed. This research used the qualitative method; the researcher as the main instrument collected data in the field. Data collection was conducted through observation, interview, and documentation; data analysis was done according to the focus of the research. The research result was the decoration and calligraphy writing on Shadrul Akabir ‘Abdullah’s tomb gave the sign that Hindu and Islamic cultures existed in two conceptions. Keywords: decoration, calligraphy, shadrul akabir ‘abdullah’s tomb, aceh ABSTRAK Makam Shadrul Akabir ‘Abdullah merupakan salah satu peninggalan kerajaan Samudera Pasai. Makam tersebut didatangkan dari Gujarat sekitar abad ke-15. Ornamen pada makam ini merupakan percampuran dua kebudayaan yaitu kebudayaan Hindu dan Islam. Perpaduan antara dua kebudayaan Hindu dan Islampada makam Shadrul Akabir ‘Abdullah dapat dilihat pada ornamen dan tulisan kaligrafi.Makam ini memilikinilai sejarah melalui tulisan kaligrafi;dapat menggungkap sejarah masuknya Islam ke Aceh.Persentuhan dua kebudayaan tersebut meninggalkan jejak-jejak kebudayaan yang menarik untuk diungkapkan. Penelitian ini menggunakan metode kualitatif; penelitii sebagai instrumen utama mengumpulkan data di lapangan. Pengumpulan data dilakukan melalui observasi, wawancara, dokumentasi; analisis data dilakukan sesuai dengan fokus penelitian. Hasil; hiasan dan tulisan kaligrafi pada makam Shadrul Akabir ‘Abdullah memberikan pertanda bahwa kebudayaan Hindu dan Islam eksis dalam dua konsepsi.